Dendritic Cell Subsets and Effector Function in Idiopathic and Connective Tissue Disease-Associated Pulmonary Arterial Hypertension - van Uden, Denise; Boomars, Karin; Kool, Mirjam (Frontiers in Immunology, 2019)
Pulmonary arterial hypertension (PAH) is a cardiopulmonary disease characterized by an incurable condition of the pulmonary vasculature, leading to increased pulmonary vascular resistance, elevated pulmonary arterial pressure resulting in progressive right ventricular failure and ultimately death. PAH has different underlying causes. In approximately 30-40% of the patients no underlying risk factor or cause can be found, so-called idiopathic PAH (IPAH). Patients with an autoimmune connective tissue disease (CTD) can develop PAH (CTD-associated PAH (CTD-PAH)), suggesting a prominent role of immune cell activation in PAH pathophysiology. This is further supported by the presence of tertiary lymphoid organs (TLOs) near pulmonary blood vessels in IPAH and CTD-PAH. TLOs consist of myeloid cells, like monocytes and dendritic cells (DCs), T-cells, and B-cells. Next to their T-cell activating function, DCs are crucial for the preservation of TLOs. Multiple DC subsets can be found in steady state, such as conventional DCs (cDCs), including type 1 cDCs (cDC1s) and type 2 cDCs (cDC2s), AXL+Siglec6+ DCs (AS-DCs) and plasmacytoid DCs (pDCs). Under inflammatory conditions monocytes can differentiate into monocyte-derived-DCs (mo-DCs). DC subset distribution and activation status play an important role in the pathobiology of autoimmune diseases and most likely in the development of IPAH and CTD-PAH. DCs can contribute to pathology by activating T-cells (production of pro-inflammatory cytokines) and B-cells (pathogenic antibody secretion). In this review we therefore describe the latest knowledge about DC subset distribution, activation status and effector functions, and polymorphisms involved in DC function in IPAH and CTD-PAH to gain a better understanding of PAH pathology.